Silk fibroin-sophorolipid gelation: deciphering the underlying mechanism - Dubey, Parul; Kumar, Sugam; Aswal, Vinod K.; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Prabhune, Asmita; Nisal, Anuya (Biomacromolecules, 2016)
Silk fibroin (SF) protein, produced by silkworm Bombyx mori, is a promising biomaterial, while sophorolipid (SL) is an amphiphilic functional biosurfactant synthesized by nonpathogenic yeast Candida bombicola. SL is a mixture of two forms, acidic (ASL) and lactonic (LSL), which when added to SF results in accelerated gelation of silk fibroin. LSL is known to have multiple biological functionalities and hence hydrogels of these green molecules have promising applications in the biomedical sector. In this work, SANS, NMR, and rheology are employed to examine the assembling properties of individual and mixed SLs and their interactions with SF to understand the mechanism that leads to rapid gelation. SANS and NMR studies show that ASL assembles to form charged micelles, while LSL forms micellar assemblies and aggregates of a mass fractal nature. ASL and LSL together form larger mixed micelles, all of which interact differently with SF. It is shown that preferential binding of LSL to SF causes rapid unfolding of the SF chain leading to the formation of intermolecular beta sheets, which trigger fast gelation. Based on the observations, a mechanism for gelation of SF in the presence of different sophorolipids is proposed.

pH dependent sophorolipid assemblies and their influence on gelation of silk fibroin protein - Dubey, Parul; Kumar, Sugam; Ravindranathan, Sapna; Vasudevan, Sahana; Aswal, Vinod K.; Rajamohanan, Pattuparambil R.; Nisal, Anuya; Prabhune, Asmita (Materials Chemistry and Physics, 2018)
Sophorolipid (SL), a bio-derived surfactant is an excellent gelling agent for natural fibrous protein, silk fibroin (SF) leading to potential biomedical applications. Interaction of SF with SL has been shown to accelerate the formation of hydrogel with the rate being dependent on the form of SL used. Here, we examine the effect of pH on SL-SF interaction and gel formation by employing rheology, fluorescence spectroscopy, SANS and NMR. The results indicate that the size of SL assemblies decrease as pH increases from acidic to alkaline and significantly impacts the association of SL and SF. The association of SF and SL is mainly via hydrophobic interactions, with the SL molecules forming bead like structures along the SF chain. The increased charge on the acidic form of SL at higher pH results in greater repulsion between acidic SL molecules, which are bound to the hydrophobic sites of SF, leading to rapid chain unfolding and subsequent gelation. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Assemblies; Nuclear magnetic resonance spectroscopy; pH; Silk fibroin; Small angle neutron scattering; Sophorolipid

Visible light-responsive composition-dependent morphology and cargo release in mixed micelles of dendron amphiphiles - Avhad, Shankarrao V.; Kumar, Sugam; Ambade, Ashootosh V. (Langmuir, 2025)
2,2-Bis-(methylol)propionic acid-based second-generation polyester dendron amphiphile (T-D) containing visible light-responsive donor-acceptor Stenhouse adduct (DASA) as hydrophobic tails is synthesized. Micelles of T-D amphiphile and its mixed micelles of varying compositions with nonresponsive dendron amphiphile containing lauryl groups are prepared in aqueous solution. In transmission electron microscopy and atomic force microscopy analyses, T-D amphiphiles show rice grain-like ellipsoidal micelles as the predominant morphology. Mixed micelles display a composition-dependent morphology gradient such that the morphology changes from rice grain like to mixed to completely spherical with decreasing content of the T-D amphiphile. Complete morphology change to spherical micelles and partial reversal to ellipsoidal micelles, finally leading to ill-defined aggregates, are observed when the T-D amphiphile micelles are subjected to visible light-dark storage photoswitching cycles. Small-angle neutron scattering (SANS) analysis of 1 wt.% micellar solution in THF:water (10:90) reveals only a minor change in shape and size upon photoirradiation, and the data could be fitted to spherical or ellipsoidal model. Release of hydrophobic dye from mixed micelles is tuned by the content of the photoresponsive amphiphile. Cellular uptake and visible light-triggered release of hydrophobic drug from mixed micelles are demonstrated using MDA-MB-231 cells, suggesting their applicability for photoresponsive drug delivery.